Nanophytoplankton and microphytoplankton in the western tropical Pacific Ocean: its community structure, cell size and carbon biomass - Yan, Wenzhuo; Chen, Zhuo; Zhang, Linlin; Wang, Feng; Zhang, Guicheng; Sun, Jun (Frontiers in Marine Science, 2023)
Community structure, cell size and carbon biomass of phytoplankton in the western Pacific Ocean in 2019 were investigated. This is the first report of phytoplankton in the western Pacific Ocean using Utermöhl and carbon-volume conversion methods. Phytoplankton consisted mainly of dinoflagellates (181 species), diatoms (73 species), cyanobacteria (4 species) and chrysophyceae (2 species). Cyanobacteria were abundant in section B (1°-20°N, 141°E). Dinoflagellates were evenly distributed in the survey area. Wind stress-induced shallowing of the thermocline and terrestrial influences lead to increased diatom abundance. Quantile regression of cell size revealed that most phytoplankton had equivalent spherical diameters of 2-12 µm, while others were 12-25 µm, and phytoplankton larger than 25 µm were rare. Nanophytoplankton (2-20 µm) dominated cell abundance, but they contributed 376.324 mg m-3 of carbon, while microphytoplankton (20-200 µm) contributed 792.295 mg m-3. Phytoplankton species of the weatern Pacific Ocean can be divided into four groups according to the results of CCA: High temperature, strong light and low nutrient group; Low temperature, weak light and high nitrate group; High temperature, strong light group; Low temperature and low nitrate group. The first group is the main species, including Trichodesmium thiebautii, Ceratium teres and Scrippsiella trochoidea.